Anthropogenic Signatures of Lead in the Northeast Atlantic. Issue 6 (23rd March 2018) - Rusiecka, D.; Gledhill, M.; Milne, A.; Achterberg, E. P.; Annett, A. L.; Atkinson, S.; Birchill, A.; Karstensen, J.; Lohan, M.; Mariez, C.; Middag, R.; Rolison, J. M.; et al.
Abstract: Anthropogenic activities have resulted in enhanced lead (Pb) emissions to the environment over the past century, mainly through the combustion of leaded gasoline. Here we present the first combined dissolved (DPb), labile (LpPb), and particulate (PPb) Pb data set from the Northeast Atlantic (Celtic Sea) since the phasing out of leaded gasoline in Europe. Concentrations of DPb in surface waters have decreased by fourfold over the last four decades. We demonstrate that anthropogenic Pb is transported from the Mediterranean Sea over long distances (>2, 500 km). Benthic DPb fluxes exceeded the atmospheric Pb flux in the region, indicating the importance of sediments as a contemporary Pb source. A strong positive correlation between DPb, PPb, and LpPb indicates a dynamic equilibrium between the phases and the potential for particles to "buffer" the DPb pool. This study provides insights into Pb biogeochemical cycling and demonstrates the potential of Pb in constraining ocean circulation patterns. Plain Language Summary: Lead (Pb) is a toxic element to all living organisms and may cause health impacts upon exposure to high levels. Humans have introduced large amounts of Pb into environment over last 150~years mainly through combustion of leaded gasoline and coal. The anthropogenic Pb is transported over long distances in the atmosphere and deposited in remote ocean regions resulting in elevated Pb concentrations. Since the implementation of stricter environmental regulations over last decades, Pb levels in surface waters have declined. In this study we report five times lower Pb concentrations in European surface waters compared with those from the 1980s and also present recent Pb inputs. Once anthropogenic Pb is introduced into the marine environment, it can be used to trace specific water mass transport throughout the global ocean. In this study we use Pb signal to demonstrate transport of Mediterranean Sea surface water over 2, 500~km across the Atlantic Ocean. Our results serve as evidence of the positive impact of environmental regulations on Pb inputs and highlight the requirement of continuing efforts in regulating Pb emissions. Key Points: Recent sources of Pb were evident despite a fourfold reduction of Pb in NE Atlantic surface waters since leaded gasoline prohibition Enhanced Pb was evident in Mediterranean Outflow Waters, transported >2, 500 km across the NE Atlantic Sediments represented an important source of Pb to overlying waters, exceeding the atmospheric flux of Pb